2015
DOI: 10.1007/s40011-015-0644-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Antioxidant Potential of Aegle marmelos Fermented Fruit Juice

Abstract: Aegle marmelos fruit, leaf and bark, are traditionally used for treatment of diabetes, liver toxicity, fungal infection, microbial infection, inflammation and pyrexia. In the present study, an attempt has been made to ferment the A. marmelos fruit juice and evaluate its nutritional and antioxidant potential as well as its sensory attributes. The nutritional potential of the fermented fruit juice showed an increased level of titratable acidity and lactic acid content of 1.7 g tartaric acid/L and 7.2 mg/L respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…According to Karumaran et al (2016), the antioxidants present in A. marmelos are better extracted in methanol or polar solvent, which can be related to our study since both the ethyl acetate extract of leaf and bark has a minimum scavenging activity. Patra et al (2017), revealed the presence of β-carotene, lycopene and ascorbic acid in the fermented fruit juice of A. marmelos with 81% DPPH inhibition percentage which is comparable to our ethanolic extract. In contrast, Prakash et al (2011) reported antioxidant activity and TPC value of fruit pulp to be 58.1% and 26.3 respectively, which is lower than our result.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…According to Karumaran et al (2016), the antioxidants present in A. marmelos are better extracted in methanol or polar solvent, which can be related to our study since both the ethyl acetate extract of leaf and bark has a minimum scavenging activity. Patra et al (2017), revealed the presence of β-carotene, lycopene and ascorbic acid in the fermented fruit juice of A. marmelos with 81% DPPH inhibition percentage which is comparable to our ethanolic extract. In contrast, Prakash et al (2011) reported antioxidant activity and TPC value of fruit pulp to be 58.1% and 26.3 respectively, which is lower than our result.…”
Section: Discussionsupporting
confidence: 80%
“…The bark decoction was used to treat fever and cough. The fruit pulp of A. marmelos contains tannin, amino acids, lignin, proteins, gallic acid, quercetin, and chlorogenic acid (Patra et al, 2017;Prakash et al, 2011).…”
mentioning
confidence: 99%
“…Braga, Mesquita, Martins, Habu, and Rosso (2018) reported that the ABTS free‐radical scavenging activity of jussara pulp increased after fermentation with several different species of lactic acid bacteria. In the study by Patra, Sahoo, and Swain (), the ABTS free‐radical scavenging capacity of Aegle marmelos juice increased significantly after fermentation with S. cerevisiae . These results are consistent with the present results.…”
Section: Resultsmentioning
confidence: 96%
“…The diluted bael pulp was improved with sugar and acid and fermented at 30±2 0 C using the yeast Saccharomyces cerevisiae [4]. Patra et al [5] reported fermented bael juice contains titrable acidity and lactic acid with 1.7mg tartaric acid/L and 7.2mg/L, respectively. It is rich in antioxidants and can be utilised as a medicinal drink with significant nutritional potential.…”
Section: Introductionmentioning
confidence: 99%